Diuretic or sodium-restricted diet for obstructive sleep apnea—a randomized trial. Issue 4 (30th January 2018) - Fiori, Cintia Zappe; Martinez, Denis; Montanari, Carolina Caruccio; Lopez, Pedro; Camargo, Rodrigo; Sezerá, Lauren; Gonçalves, Sandro Cadaval; Fuchs, Flavio Danni
Abstract: Study Objectives: Interventions that decrease leg fluid retention reduce obstructive sleep apnea (OSA) severity in nonrandomized experiments. We aimed to investigate in a randomized trial the effect of interventions that reduce fluid volume on OSA severity. Methods: Men diagnosed with severe OSA were randomized to receive daily spironolactone 100 mg + furosemide 20 mg or nutritional counseling to sodium-restricted diet plus placebo pill or placebo pill. All participants underwent home sleep apnea testing at baseline and after 1 week follow-up. The change in apnea–hypopnea index (AHI) was the primary outcome. Results: The study included 54 participants and all were assessed at follow-up. The average baseline value of the AHI was similar among groups and from baseline to follow-up the AHI reduced 14.4 per cent (δ value −7.3 events per hour; 95% confidence interval, −13.8 to −0.9) in the diuretic group, 22.3 per cent (−10.7; 95% CI, −15.6 to −5.7) in the diet group, and 0.8 per cent (0.4; 95% CI, −2.5 to 3.2) in the placebo group ( p = .001 for time × group interaction). None of the patients had their AHI returned to normal. The reduction in the total body water was 2.2 ± 2.2 L in the diuretic group ( p < .001) and 1.0 ± 1.6 l in the low salt diet group ( p = .002). Sleepiness and neck circumference were significantly reduced only in the diet group ( p = .007 and p < .001 for the time × group interactions, respectively). Conclusions: Interventions to reduce bodily fluid content in men with severe OSA promoted a limited decrease of apnea frequency. This finding suggests that rostral fluid displacement affects only partially the OSA severity and/or that other factors prevail in determining pharyngeal collapsibility. Clinical Trial: Sodium-Restricted Diet and Diuretic in the Treatment of Severe Sleep Apnea (DESALT), https://clinicaltrials.gov/ct2/show/NCT01945801 ClinicalTrials.gov number: NCT01945801.